Socio-Economic Analysis of Fresh Fish Traders During The COVID-19 Pandemic at The Rajawali TPI Makassar City - Salsabilah, Juwarsi Auliya; Amiluddin, Amiluddin; Cangara, Arie Syahruni; Baso, Aris; Gosari, Benny Audy Jaya (PONGGAWA : Journal of Fisheries Socio-Economic, 2021)
This study aims to determine changes in social conditions which include group dynamics and social concerns as well as to find out changes in economic conditions including marketing of fishery products, number of buyers, and income of fresh fish traders at TPI Rajawali during the COVID-19 pandemic. This research was conducted from September 2020 to October 2020, at Fresh Fish Traders in TPI Rajawali During the Covid-19 Pandemic in the City of Makassar, South Sulawesi. The sampling method was purposive sampling by selecting fresh fish traders who carried out trading activities before the Covid-19 pandemic struck and after the Covid-19 pandemic took place with a total sample size of 35 fresh fish traders. Sources of data used in this study are primary data and secondary data. Social conditions were analyzed using qualitative descriptive analysts, while for economic conditions the marketing channels were analyzed using qualitative descriptive, marketing margins, total buyers were analyzed using descriptive statistics, and income was analyzed by income analysis. The results of research on social conditions that include social interactions, social adaptation and social group dynamics during the COVID-19 pandemic have each changed. For the marketing channels at TPI Rajawali, four marketing channels were obtained and for the Marketing Margin, the average fish trader at TPI Rajawali experienced a decline due to reduced purchasing power. The results of research on the income of fresh fish traders at TPI Rajawali also decreased during the COVID-19 pandemic from Rp. 9,635,540.63 with a percentage of 56.12% decreased by Rp. 7,532,814.88 with a percentage of 43.88%.